GE_GERICHTE C/19313/2016 vom 14. September 2018 - GE Cour de justice (2018)
LIQUIDATION DU RÉGIME MATRIMONIAL ; NOUVEAU MOYEN DE FAIT ; PREUVE ; CONCLUSIONS ; OBLIGATION D'ENTRETIEN ; LOYER | CPC.58.al1;